2021
DOI: 10.7554/elife.68215
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal calcium sensor Synaptotagmin-1 and SNARE proteins cooperate to dilate fusion pores

Abstract: All membrane fusion reactions proceed through an initial fusion pore, including calcium-triggered release of neurotransmitters and hormones. Expansion of this small pore to release cargo is energetically costly and regulated by cells, but the mechanisms are poorly understood. Here we show that the neuronal/exocytic calcium sensor Synaptotagmin-1 (Syt1) promotes expansion of fusion pores induced by SNARE proteins. Pore dilation relied on calcium-induced insertion of the tandem C2 domain hydrophobic loops of Syt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 164 publications
4
26
0
Order By: Relevance
“…Because simultaneous monitoring of content release and lipid mixing shows that most fusion pores reseal after partial content release in a similar assay ( Stratton et al, 2016 ), the intensity changes observed by Kiessling et al (2010) more likely represent diffusion of the lipid labels from the SUV into the SBL with the SUV retaining an omega-shape until the lipids are dispersed into the SBL. This would be an interpretation consistent with observations of secretory granule exocytosis in neuroendocrine cells ( Taraska et al, 2003 ; Tran et al, 2007 ; Anantharam et al, 2010 ; Anantharam et al, 2012 ; Chiang et al, 2014 ; Karatekin, 2018 ; Shin et al, 2018 ), enveloped viral fusion events ( Melikyan et al, 1993a ; Melikyan et al, 1993b ; Melikyan et al, 1995 ; Cohen and Melikyan, 2004 ), and other reconstitutions with artificial membranes with sufficient resolution to monitor fusion pore dynamics ( Chanturiya et al, 1997 ; Lai et al, 2013 ; Wu et al, 2016 ; Wu et al, 2017 ; Wu et al, 2021 ), where pore flickering and slow changes in the -shape of the vesicle appear to be the norm.…”
Section: Discussionsupporting
confidence: 86%
“…Because simultaneous monitoring of content release and lipid mixing shows that most fusion pores reseal after partial content release in a similar assay ( Stratton et al, 2016 ), the intensity changes observed by Kiessling et al (2010) more likely represent diffusion of the lipid labels from the SUV into the SBL with the SUV retaining an omega-shape until the lipids are dispersed into the SBL. This would be an interpretation consistent with observations of secretory granule exocytosis in neuroendocrine cells ( Taraska et al, 2003 ; Tran et al, 2007 ; Anantharam et al, 2010 ; Anantharam et al, 2012 ; Chiang et al, 2014 ; Karatekin, 2018 ; Shin et al, 2018 ), enveloped viral fusion events ( Melikyan et al, 1993a ; Melikyan et al, 1993b ; Melikyan et al, 1995 ; Cohen and Melikyan, 2004 ), and other reconstitutions with artificial membranes with sufficient resolution to monitor fusion pore dynamics ( Chanturiya et al, 1997 ; Lai et al, 2013 ; Wu et al, 2016 ; Wu et al, 2017 ; Wu et al, 2021 ), where pore flickering and slow changes in the -shape of the vesicle appear to be the norm.…”
Section: Discussionsupporting
confidence: 86%
“…However, the molecular mechanism by which Syt1 drives membrane fusion is yet not completely understood. 13,20…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism by which Syt1 drives membrane fusion is yet not completely understood. 13,20 In the present work, we use enhanced molecular dynamics with an ad hoc collective variable to induce a fusion stalk between lipid bilayers. We demonstrate that Syt1-C2B domains cooperatively facilitate the formation of the fusion stalk, a Instituto de Histología y Embriología de Mendoza (IHEM) -Consejo Nacional de Investigaciones Cientícas y Técnicas (CONICET), Universidad Nacional de Cuyo (UNCuyo), 5500, Mendoza, Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Because simultaneous monitoring of content release and lipid mixing shows that most fusion pores reseal after partial content release in a similar assay (Stratton et al, 2016), the intensity changes observed by Kiessling et al (2010) more likely represent diffusion of the lipid labels from the SUV into the SBL with the SUV retaining an omega-shape until the lipids are dispersed into the SBL. This would be an interpretation consistent with observations of secretory granule exocytosis in neuroendocrine cells (Taraska et al, 2003;Tran et al, 2007;Anantharam et al, 2010;Anantharam et al, 2012;Chiang et al, 2014;Karatekin, 2018;Shin et al, 2018), enveloped viral fusion events (Melikyan et al, 1993a;Melikyan et al, 1993b;Melikyan et al, 1995;Cohen and Melikyan, 2004), and other reconstitutions with artificial membranes with sufficient resolution to monitor fusion pore dynamics (Chanturiya et al, 1997;Lai et al, 2013;Wu et al, 2016;Wu et al, 2017;Wu et al, 2021), where pore flickering and slow changes in the Ω-shape of the vesicle appear to be the norm.…”
Section: Discussionsupporting
confidence: 84%